KEDUDUKAN DAN PERAN ANGGOTA DEWAN PEREMPUAN DALAM FUNGSI LEGISLASI DI DPRD KABUPATEN CILACAP PERIODE 2009-2014 - Lestari, Hany (Unnes Civic Education Journal, 2017)
Abstract: This study aims to describe the position and the role of women in doing the function of legislation in the DPRD Kabupaten Cilacap 2009-2014 period. The analysis is performed using interactive qualitative analysis. The result that is gained in this research shows that the position of councilwomen in the DPRD Kabupaten 2009-2014 period is still marginal politically. The role of the councilwomen in the implementation of the function of legislation in the DPRD Kabupaten Cilacap 2009-2014 period does not seem maximum. The position or the office of councils influences the role of councils either the councilwomen or the councilmen especially in the implementation of the function of legislation in the DPRD Kabupaten Cilacap 2009-2014 period. The suggestion of this research is that it needs the upgrading of skills and self-quality of the councilwomen in order to be able to do the duty and the function well as the local council in the DPRD Kabupaten Cilacap, it needs the upgrading of awareness and sensitivity from the councilwomen in order to be able to represent the aspiration of women, it needs the endorsement from either the councilmen or the executive party in the implementation of the fucntion of legislation in order to create rewarding legal products for the interests of many people and the people themselves need to get socialization in order not to be stuck in the system of patriarchy, so that it will create the equality between women and men in every aspect of the social life.